Treatment Guidelines for Rare, Early-Onset, Treatment-Resistant Epileptic Conditions: A Literature Review on Dravet Syndrome, Lennox-Gastaut Syndrome and CDKL5 Deficiency Disorder - Chin, Richard F.; Mingorance, Ana; Ruban-Fell, Benjamin; Newell, Isabelle; Evans, Jenni; Vyas, Kishan; Nortvedt, Charlotte; Amin, Sam (Frontiers in Neurology, 2021)
Background Dravet syndrome (DS), Lennox-Gastaut syndrome (LGS) and CDKL5 deficiency disorder (CDD) are rare epileptic conditions, characterised by drug-resistant seizures. Seizure management in these patients requires careful therapy selection. This targeted literature review (TLR) aimed to collate and synthesise information from country-specific and international treatment guidelines for DS, LGS and CDD. Methods A TLR was performed between 25th January and 11th March 2021. Online rare diseases and guideline databases were manually searched in addition to websites of national health technology assessment bodies for the following countries: Australia, Canada, France, Germany, Israel, Italy, Japan, Spain, Switzerland, UK and US, as defined by pre-specified eligibility criteria. Search terms, developed for each condition, were translated into local languages where appropriate. Descriptive analyses were performed to examine the geographical distribution of included guidelines; methodologies used to develop guidelines; cross-referencing of treatment recommendations made within other guidelines; patterns of treatment recommendations. An author map was created using R version 3.5.1, to visualise the extent of collaboration between authors. Results 40 total guidelines were included, of which 29, 34 and 0 contained recommendations for DS, LGS and CDD, respectively (some provided recommendations for ≥1 condition). Most were country-specific, with guideline authors predominantly publishing in regional groups. Five guidelines were classified as “International” and displayed connections between author groups in the US, UK, France and Italy. Reported guideline development processes were lacking (43% [17 guidelines] had unclear/absent literature review methodologies) and those reported were variable, including both systematic and targeted literature reviews. Use of expert consultation was also variable. A high degree of heterogeneity was observed in the availability of treatment recommendations across disorders, with 271 and 190 recommendations for LGS and DS, respectively, and contradictory positive and negative treatment recommendations for several drugs in each indication (35% [11/31] and 22% [6/27] in LGS and DS, respectively). Conclusions This review highlights the need for further high-quality international consensus-based treatment guidelines for LGS, DS, and particularly for CDD (for which no treatment guidelines were identified). Supra-national consensus guidance based on findings from a wider geographical range may improve resource allocation and establish an improved world-wide standard of care.